Ecology and diversity of zooplankton in relation to physico-chemical characteristics of water of Santragachi Jheel, West Bengal, India - Patra, Ashis; Santra, Kalyan Brata; Manna, Chanchal Kumar (Journal of Wetlands Ecology, 2011)
In the present study efforts have been made to ascertain the seasonal abundance and population dynamics of zooplankton community and its relationship with physico-chemical factors of the water bodies of Santragachi Jheel in the District Howrah, W.B., INDIA. The zooplankton abundance showed distinct seasonal or temporal variation in the Jheels. A total of 18 species belonging to 12 families and 15 genera were recorded. The population density of total zooplankton showed summer maxima in the Jheel. Maximum abundance of rotifer fauna was recorded during summer season in sewage sites whereas Cladocera population showed maximum density at non-sewage sites. Copepods showed postmonsoon maxima in sewage sites in the Jheels. Some species i.e., Polyarthara vulgaris were quite abundant in the polluted water of the Santragachi Jheel. Out of 15 genera of Zooplankton, Brachionus, Keratella, Polyarthra, Diaphanosoma, Ceriodaphnia, Bosmina, Heliodiaptomus and Mesocyclops were found to be dominant in Santragachi Jheel. Highest percentage of similarity was recorded between S1 and S3 sites of the Jheel. Results of ANOVA (2 - way) indicated that zooplankton population differs significantly in relation to stations and seasons of the Jheel. Population of Rotifera, the most dominant group was found to be positively influenced by Biological Oxygen demand (BOD), Free Carbon-di-oxide FCO2), CaCO3 hardness (CaHa), Total suspended solid (TSS), Chloride(Cl) and Phosphate (PO4) in the Jheels. Total Cladocera showed positive correlation with PO4 in the Jheel. The Copepods expressed positive correlation with BOD and ammonia. Increment of population density of several zooplankton organisms (i.e., Keratella tropica, Polyarthra vulgaris) and low value of community indices especially species diversity and species richness indicated the rise of pollutional stress on the Santragachi Jheel. Keywords: Zooplankton; Rotifera; BOD; COD; Shannon - Wiener index; Evenness index DOI: http://dx.doi.org/10.3126/jowe.v5i0.4595 J Wet Eco 2011 (5): 20-39